Determinan Perilaku Konsumtif Generasi Z Muslim di Era Digital - Okta Febriansyah; Herlina Yustati; Eeng Juli Efrianto (Universitas Muhammadiyah Surabaya, 2026)
This study aims to analyze the various determinants of consumer behavior among Generation Z Muslims in Pagar Dewa Village, Bengkulu City. The variables tested as determinants in this study include hedonic lifestyle, self-control, and peer environment. The method used was a quantitative approach with a causal associative research approach. Primary data were collected through questionnaires from a sample of 2,836 people using quota sampling. Data analysis was performed using multiple linear regression using SPSS version 29 software. The results showed that partially, hedonic lifestyle and peer environment were determinants with a positive and significant influence on consumer behavior. However, self-control was found to have a significant positive influence, thus disproving the initial assumption that self-control was a negative determinant of consumer behavior. Simultaneously, these three variables were significant determinants influencing consumer behavior, contributing 47.1%.